2017
DOI: 10.1097/ijg.0000000000000599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclopentolate on In Vivo Schlemm Canal Microarchitecture in Healthy Subjects

Abstract: Cyclopentolate causes a reduction in SC dimensions in healthy eyes. Future studies are warranted to determine the exact mechanism(s) of this change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The resolution offered by today's OCT imaging devices has allowed clinicians to identify aqueous humour outflow structures, including the SC, as already described by many authors in healthy adults or those with glaucoma (Kagemann et al 2010; Usui et al 2011;Shi et al 2012;Chen et al 2013;Hong et al 2013Hong et al , 2014Skaat et al 2016Skaat et al , 2017Rosman et al 2017;Kuerten et al 2018).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The resolution offered by today's OCT imaging devices has allowed clinicians to identify aqueous humour outflow structures, including the SC, as already described by many authors in healthy adults or those with glaucoma (Kagemann et al 2010; Usui et al 2011;Shi et al 2012;Chen et al 2013;Hong et al 2013Hong et al , 2014Skaat et al 2016Skaat et al , 2017Rosman et al 2017;Kuerten et al 2018).…”
Section: Discussionmentioning
confidence: 94%
“…), cyclopentolate (Rosman et al. ), trabeculoplasty (Skaat et al. ), canaloplasty (Grieshaber et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although cyclopentolate agents do not cause as much pupil dilation as other mydriatic agents do, several studies indicated that the use of 1% cyclopentolate agents might lead to little increase in the IOP. 17,18 However, the effect of 0.5% cyclopentolate has not been addressed. It is not clear whether or not there would be an increase in the IOP measurements when 0.5% cyclopentolate is administrated.…”
Section: Introductionmentioning
confidence: 99%
“…The topically applied cycloplegic drops inducing both mydriasis and cycloplegia are widely used for detailed fundus examinations and cycloplegic refraction in outpatient clinic [1]. Cyclopentolate and tropicamide are the most commonly applied cycloplegic drops in clinics.…”
Section: Introductionmentioning
confidence: 99%